Using tasks to bring challenge in mathematics classroom - Ioannis Papadopoulos (Journal of Pedagogical Research, 2020)
Rich and challenging tasks can be the vehicle to bring mathematical challenge in classroom. Challenge emerges when you don't know how to solve the task at first but you can figure out, that is when the solvers are not aware of certain tools to solve the tasks and they have therefore to invent some mathematical actions to proceed. Some challenging tasks in the paper-and-pencil as well as in a digital environment will be presented. The aim is to highlight their potential (i) in engaging students to actions that make sense for them from the mathematical point of view, (ii) to support students in their experimentation and development of problem-solving strategies, (iii) to foster creative mathematical thinking, and (iv) to provoke students' curiosity as the starting point of meaning-making actions in mathematics.